Analisis Kinerja Perusahaan dan Kinerja Saham Perusahaan sebelum dan sesudah memperoleh Sertifikasi ISO 9001:2000: Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia - Wilopo, R.; Priyambodo, Agung (Universitas Brawijaya, Indonesia, 2008)
The main obyective of this study is to compare companies performance, before and after getting ISO 9001: 2000 certificate. The other aim is to observe investor's response about the company getting ISO 9001: 2000 certificate. The research population is the manufacture firm going public in Indonesia Capital Market. The samples are 23 companies and observation periods are from 2000 to 2006. The research finds that there is not differencies of financial performance before and after the companies getting ISO 9001: 2000. It's means that ISO 9001: 2000 is only a management tool to show a improvement of quality management systems, but without being followed by increase of financial performance. Altough there is not financial performance differencies, but the announcement of ISO 9001: 2000 gives positive response to investor about good news of quality management improvement in the company. The response is declared by the differencies of stock return before and after the company samples get ISO 9001: 2000 certificate. There is a improvement of stock return after the companies samples ger ISO 9001: 2000.